Analisis Kelayakan Industri Rumah Tangga Pengolahan Asam Gelugur Menjadi Asam Potong Di Kecamatan Biru-Biru Kabupaten Deli Serdang - Michael Valentino Gulo; Sri Ariani Safitri (Universitas Medan Area, 2026)
This study aims to identify the feasibility of a home industry processing asam gelugur into asam potong in Biru-Biru District, Deli Serdang Regency. Asam gelugur is a cooking ingredient that is first processed into asam Potong which is then used to add flavor to dishes, especially to add sourness to food. The business of processing asam gelugur into asam Potong in Biru-biru District is a mainstay of the community's economy so it needs to be developed. This study analyzes with a quantitative approach using primary data. The method used in this study is to use the Revenue Cost Ratio (R/C) and Benefit Cost Ratio (B/C) formulas. This study concludes that the average income of asam gelugur processors reaches IDR 2,554,560 per month with a Revenue Cost Ratio (R/C) value of 2.11 and a Benefit Cost Ratio (B/C) value of 1.11 which states that the business is feasible to run, because it meets the requirements that the value of the Revenue Cost ratio (R/C) and Benefit Cost Ratio (B/C) 1.